(untitled) (Jurnal Manajemen dan Kewirausahaan, 2015)
The objective of this research is to determine the effects of minimum service standard on passengers’ satisfaction, the strategy application and the performance of Transjakarta Company. Questionnaires are distributed to 200 respondents. The form of research is descriptive and verificative. The research model is multiple regression with the Likert scale. The results of this research show that minimum service standard (reliability, security and safety, convenience and comfort) simultaneously affect passengers’ satisfaction. Reliability and comfort partially affect passengers’ satisfaction. Security and safety, and convenience do not affect passengers’ satisfaction. The strategy application uses importance performance analysis (IPA). The strategies are 1) Conducting continuous improvements to increase attribute performance 2) Maintaining good performance; 3) Managing seriously in order not to incite passengers’ disappointment; 4) Evaluating all excessive activities.